From Cannabis sativa to Cannabidiol: Promising Therapeutic Candidate for the Treatment of Neurodegenerative Diseases - Cassano, Tommaso; Villani, Rosanna; Pace, Lorenzo; Carbone, Antonio; Bukke, Vidyasagar Naik; Orkisz, Stanislaw; Avolio, Carlo; Serviddio, Gaetano (Frontiers in Pharmacology, 2020)
Cannabis sativa, commonly known as marijuana, represents a reservoir of compounds exerting beneficial properties. Besides Δ9-tetrahydrocannabinol that is responsible for the psychotropic effect associated with Cannabis consumption, cannabidiol (CBD) is the most abundant nonpsychoactive phytocannabinoid and may represent a prototype for anti-inflammatory drug development for human pathologies where is involved the activation of immune system and oxidative stress (OS), as a contributor to their aetiology and progression. To this regard, OS has been implicated in the progression of a number of neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD). These diseases are characterized by extensive oxidative damage to different biological substrates that can lead to cell death by a variety of different mechanisms. Most cases of neurodegenerative diseases have a complex aetiology with numerous genetic and environmental factors contributing to progression; therefore, biomarker and treatment strategies may require simultaneous targeting of multiple components, including some specific to disease stage, in order to assess and modulate neurodegeneration. In this context, CBD, which interacts with the endocannabinoid system, but has also cannabinoid receptor-independent mechanism, might be a good candidate as a prototype for anti-oxidant drug development. The wide range of targets of CBD emphasizes its potential as a multimodal drug for the major neurodegenerative disorders, such as PD and AD. The present review summarizes the multiple biochemical and molecular mechanisms that have been associated with the therapeutic effects of CBD that may have a considerable impact on the progression of the major neurodegenerative disorders.